ON THE PHYSICAL PROPERTIES AND ANATOMICAL FEATURES OF DAEMONOROPS ANGUSTIFOLIA AND CALAMUS ORNATUS - Latif, M., Abd; Kadir, Roszaini; Noor, Nur; Zin Jusuh, Mohd (วารสารวนศาสตร์ไทย, 2022)
This paper discusses the physical and anatomical characteristics of 17 years old Daemonorops angustifolia ‘rotan getah’ and Calamus ornatus ‘rotan dok’ collected from FRIM of Kepong, Selangor. C. ornatus had a bigger stem diameter (28 to 37 mm) but shorter in internodes length (14 to 35 cm) than D. angustifolia (20 to 27 mm and 23 to 52 cm, respectively). The initial moisture content ranged from 80.22 to 133.51% in D. angustifolia and 70.67 to 102.58% in C. ornatus. Both species had lower oven-dry density which ranged from 0.31 to 0.49 gcm-3. There were also some visible differences in the anatomical features among the species and heights of the stems studied.